Modeling of advanced accelerator concepts. (11th October 2021) - Vay, J.-L.; Huebl, A.; Lehe, R.; Cook, N.M.; England, R.J.; Niedermayer, U.; Piot, P.; Tsung, F.; Winklehner, D.
Abstract: Computer modeling is essential to research on Advanced Accelerator Concepts (AAC), as well as to their design and operation. This paper summarizes the current status and future needs of AAC systems and reports on several key aspects of (i) high-performance computing (including performance, portability, scalability, advanced algorithms, scalable I/Os and In-Situ analysis), (ii) the benefits of ecosystems with integrated workflows based on standardized input and output and with integrated frameworks developed as a community, and (iii) sustainability and reliability (including code robustness and usability).